The Use of Total Physical Response Strategy at Junior High School of SLBN South Curup, Rejang Lebong - Gusmuliana, Paidi (ENGLISH FRANCA : Academic Journal of English Language and Education, 2018)
Abstract This research aims at investigating implementation of Total Physical Response (TPR) strategy at Junior High School of SLBN Curup Selatan, for the problems came from phenomena occurred on the students with special needs who had different disability such as tunanetra/ blind students and Tunarungu/ deaf and mute students in Learning English. The objectives of this research were to find out how implementation and difficulties faced the students of using TPR strategy .Then the researcher used Qualitative research with a case study of descriptive Qualitative. The subjects were two of English teachers who managed or taught them by using TPR strategy. The techniques of collecting data in this research were observation and interview. In this case, the researcher used observation checklist and interview guidance. There were some steps to analyze the data:data reduction, data display and drawing conclusion/ verification. The result of the implementation of Total Physical Response at SMPLBN Curup Selatan that teachers could implemented Total Physical Response strategy effectively in which the students were able to receive information easily and were more enjoyable in learning English. Then the factors that could influence the difficulties for them to understanding material were from their low capacity to process information, and they need special treatment and suficient time in learning English. Key words: Total Physical Response Strategy